Management Pembelajaran IPS: Tantangan dan Ekspektasi dalam Pendidikan Karakter Peserta Didik - Ruth Sriana Umbase (Jurnal Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2022)
The problem of social studies learning management, especially in designing character education designs, presents several challenges and a series of expectations for the formation of the noble character of students. The purpose of this study is to identify and evaluate the knowledge and skills of educators in managerial aspects of learning activities which are still a challenge in designing lesson plans (RPP) and implementing and evaluating their success. The method used is the Evaluation Research Method based on the Stake's Evaluation Model, which consists of three evaluation components, namely: Antecedents, Transactions, and Outcomes. The results of this study indicate that the Antecedents component, namely environmental analysis for social studies learning planning and design, is in a low category. The Transactions component, namely the implementation of learning explicitly packaged for character education, is in the moderate category and tends to be quiet. Finally, the Outcomes component is in the intermediate class. Therefore, it is recommended to increase the knowledge and skills of educators in the Antecedents aspect through training or technical guidance on social studies learning management, especially in learning environment analysis for planning, implementation and reflection(PIR).